Perancangan Sistem Informasi Kriteria Penentuan Lokasi Gudang Sementara Untuk Bantuan Bencana Di Bpbd Jawa Barat - Ilham Muhammad Faisal; Femi Yulianti; Putu Giri Artha Kusuma (eProceedings of Engineering, 2026)
Several sub-districts in Cianjur regency stillexperience uneven distribution of aid from the threeexisting central warehouse. This issue arises because thedistribution process is concentrated in specific areas,while other sub-districts lacak clear logistics routes andbalanced delivery frequency. Such inequality can hinderthe effective delivery of aid to communities that have notyet received Adequate support. This highlights the needto carefully consider multiple criteria when selectingtemporay warehouse locations for disaster reliefdistribution. Poor location choices can significantlyreduce the effiency of aid delivery. Therefore, a thoroughanalysis of key factors – such as proximity tobeneficiaries, safety from disaster-prone areas,availability of road infrastructure, environmentalsecurity and warehouse facilities-is essential. TheAnalytical Hierarchy Process (AHP) is one method thatcan be applied to systematically and objectively assessand prioritize these criteria, enabling the selection of themost suitable warehouse locationsKata kunci— Logistik kemanusiaan, Penentuan Lokasi Gudang,Analytic Hierarchy Process, Manajemen Logistik Indonesia,Rantai Pasokan.